First reports of the invasive pest Bermudagrass Stem Maggot, Atherigona reversura Villeneuve, 1936 (Diptera: Muscidae), in South America - Patitucci, Luciano Damián (2016)
This study presents the first occurrence of Atherigona reversura in South America. This muscid, commonly known as shoot-fly, is a significant pest of cereal crops throughout the Old World tropics and subtropics. Several specimens were collected during various months in 2014 and 2015. These new records are dispersed in a wide geographical area of temperate and subtropical regions of eastern Argentina. The main host of A. reversura, the exotic bermudagrass Cynodon dactylon, is considered a pest and is widely distributed in South America.